2017
DOI: 10.1177/2158244017705423
|View full text |Cite|
|
Sign up to set email alerts
|

Construct and Concurrent Validity of thePositive Metacognitions and Positive Meta-Emotions Questionnairein the Polish Population

Abstract: The Positive Metacognitions and Positive Meta-Emotions Questionnaire (PMCEQ) of Beer and Moneta measures adaptive metacognitive beliefs when facing challenging situations. The psychometric properties of a Polish version of the PMCEQ are reported. The cultural adaptation of the instrument was conducted in a representative sample of adult Poles (n = 600). The original three-factor structure of the PMCEQ was corroborated by confirmatory factor analysis. Further psychometric analyses indicated that the instrument … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The counselor's metacognitive competence training is another alternative for novice counselors, even prospective counselors. This process provides higher-order thinking skills in thinking about what the counselor is thinking (Hanafi et al, 2020;Konarski & Brycz, 2017). In previous researchers' studies, the students counselor can also improve their metacognition by training their mind skills Hidayah, 2010;Radjah, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…The counselor's metacognitive competence training is another alternative for novice counselors, even prospective counselors. This process provides higher-order thinking skills in thinking about what the counselor is thinking (Hanafi et al, 2020;Konarski & Brycz, 2017). In previous researchers' studies, the students counselor can also improve their metacognition by training their mind skills Hidayah, 2010;Radjah, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…The MCS was assessed five times, that is, every six months. Longitudinal analysis of growth in the MCS gave greater insight into the age-related MCS changes than could be obtained from previous cross-sectional data (Konarski & Brycz, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…We believe that a strong MCS, that is, a good understanding of one's own regulatory biases, might serve a motivational role. Previous studies have shown that the MCS serves self-regulatory functions (Brycz, Jurek, Wojciechowska, Peplinska, & Bidzan 2014;Brycz, Wyszomirska-Gora, Konarski, & Wojciszke, 2018;Konarski & Brycz, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation